Floor plan of Phonse Ducey's store, Keels, NL. - Farnham, Alicia; McDougall, Claire; Morritt, Noah (2012)
Built sometime in the 1990s, Phonse Ducey’s store is typical of many mid-to-late twentieth century outbuildings in Keels. The structure is located to the southeast of Phonse and Marg’s house, adjacent to the driveway, which is located in the west section of Keels, across from St. Peter’s Anglican Church. Originally constructed for stowing firewood, the building has been used for drying squid, is occasionally used for drying fish but primarily serves as a general storage space, housing recycling, some equipment, and fire wood for the stove inside the house.